2007
DOI: 10.1002/elsc.200620177
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Adsorption Capabilities of Myriophyllum spicatum and Ceratophyllum demersum for Zinc, Copper and Lead

Abstract: Industrial wastewaters contain various heavy metal components and therefore threaten aquatic bodies. Heavy metals can be adsorbed by living or non‐living biomass. Submerged aquatic plants can be used for the removal of heavy metals. This paper exhibits the comparison of the adsorption properties of two aquatic plants Myriophyllum spicatum and Ceratophyllum demersum for lead, zinc, and copper. The data obtained from batch studies conformed well to the Langmuir Model. Maximum adsorption capacities (qmax) were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…The maximum sorption capacity is equal to filling all active locations. The authors also point out good correlations between the experimental data and calculations from the model [23,25,28,29]. The equilibrium status is also described by other isotherm models, among others, Freundlich isotherm [38] and Spis isotherm (generalised Freundlich isotherm) [28].…”
Section: Biosorption and Bioaccumulation Of Heavy Metals By Macrophytesmentioning
confidence: 75%
See 3 more Smart Citations
“…The maximum sorption capacity is equal to filling all active locations. The authors also point out good correlations between the experimental data and calculations from the model [23,25,28,29]. The equilibrium status is also described by other isotherm models, among others, Freundlich isotherm [38] and Spis isotherm (generalised Freundlich isotherm) [28].…”
Section: Biosorption and Bioaccumulation Of Heavy Metals By Macrophytesmentioning
confidence: 75%
“…The results of studies of the sorption from solutions of these metals with volume of 250 cm 3 and initial concentrations of 10 mg/dm 3 show that the time required to achieve dynamic equilibrium is approximately 20 minutes [25]. This was confirmed by other tests on the same plant species [23,26,29]; however, it is emphasised that the equilibrium status during sorption of copper in Myriophyllum spicatum is achieved after 35 minutes [30].…”
Section: Biosorption and Bioaccumulation Of Heavy Metals By Macrophytesmentioning
confidence: 77%
See 2 more Smart Citations
“…In another study, M. spicatum showed the accumulation of lead from water and the maximum adsorption 46.49 mg kg -1 (Keskinkan et al 2003). The lead adsorption capasities of M. spicatum and Ceratophyllum demersum were compared and it was observed that M. spicatum had better adsorption capacity than C. demarsum (Keskinkan et al 2007). In a study in which cadmium and lead bioaccumulation in Salvinia cucullata plant was analyzed, it was seen that the contents of cadmium and chromium were much more in the roots than in the leaves, as found in this study (Phetsombat et al 2006).…”
Section: Resultsmentioning
confidence: 93%